Legal Analysis Of The Substance Of Inheritance Law (Comparative Study Between The Indonesian Civil Code And The Dutch Civil Code) - Djumardin; HS, Salim; Sili, Eduardus Bayo (Faculty of Law, University of Mataram, 2024)
The aims to study is to examine and analyze the inheritance distribution pattern regulated in the Indonesian Civil Code, the inheritance distribution pattern according to the Dutch NBW, the differences and similarities between the inheritance distribution pattern stated in the Civil Code and the Dutch NBW, and the preparation of teaching materials for â€œInheritance Lawâ€. The inheritance law currently in force in Indonesia no longer follows the development of applicable laws worldwide. In contrast, in other countries, such as the provisions of inheritance law in the Netherlands, it has been stipulated in a new law called the Dutch NBW. Therefore, it is necessary to conduct a comparative study between Indonesian inheritance law and the Dutch NBW. The methods used are presented below. This type of research is normative legal research. The approaches used in this study are the statute and comparative approaches. The data sources come from library data, and the legal materials are primary, secondary, and tertiary. The data collection technique uses interviews and documentary studies. The data analysis uses qualitative analysis. The study results show that the heirs entitled to receive an inheritance in the Indonesian Civil Code are primarily legitimate children, illegitimate children, and the most extended surviving husband or wife. The heirs who are entitled to receive inheritance in the Dutch Civil Code consist of the husband/wife of the testator who is not separated according to law and his/her children, the parents of the testator with brothers and sisters, the grandparents of the testator; and the great-grandparents of the testator. The similarities between the heirs entitled to receive inheritance between the Indonesian Civil Code and the Dutch Civil Code are that legitimate children and husband/wife are entitled to receive inheritance.